Pengaruh Kombinasi Pupuk NPK dengan Suplemen Pupuk Organik Cair terhadap Jumlah Bakteri dan Jamur Total di Rizosfer serta Hasil Tanaman Sawi Putih (Brassica pekinensis L.) pada Andisols Lembang - Dirga Sapta Sara; Reginawanti Hindersah; Mieke Rochimi Setiawati (Soilrens, 2020)
Large P fixation on Andisols can be overcome by adding P fertilizer into soil. However, to support good plant growth required the provision of nutrients N, K, micro nutrients and hormones. Research objective was to find out effect of NPK fertilizer with liquid organic fertilizer on total bacteria and fungi in the rhizosphere and plant yield of chinesse cabage (Brassica pekinensis L.) grown in Andisols. Experiment was conducted from March until May 2011 at experimental field of PT. Multiguna Indah Lestari, Kayu Ambon village, Lembang subdistrict, Bandung regency, West Java, with altitude of 1000 m above sea levels. The experimental design was Randomized Block Design with nine treatments and three replications which consisting of combination. The fertilizer rates were without treatment (A), 1dose of NPK (B), 1 dose of liquid organic fertilizer (C), 1 dose of NPK + ½ dose of liquid organic fertilizer (D), 1 dose of NPK + ½ dose of liquid organic fertilizer (E), ½ dose of NPK + 1 dose of liquid organic fertilizer (F), ½ dose of NPK + 1 dose of liquid organic fertilizer (G), 1 dose of NPK + 1 dose of liquid organic fertilizer (H), 1 dose of NPK + 1 ½ dose of liquid organic fertilizer (I). The results showed that NPK fertilizers and liquid organic fertilizer influenced total bacterial as well as fungi in the rhizosphere and plant yield of chinesse cabage. Fertilization treatments that demonstrated the best effect on both microbial population and chinese cabbage yield was application of ½ recommended dose of NPK with 1 recomended dose of liquid organic fertilizer gives the best result of 54,72 kg per plot (54,18 ton ha-1).